Impact of the feedback provided by a gastric electrical stimulation system on eating behavior and physical activity levels. Issue 3 (6th February 2017) - Busetto, Luca; Torres, Antonio J.; Morales‐Conde, Salvador; Alarcón del Agua, Isaias; Moretto, Carlo; Fierabracci, Paola; Rovera, Giuseppe; Segato, Gianni; Rubio, Miguel A.; Favretti, Franco
Abstract : Objective: The closed‐loop gastric electrical stimulation (CLGES) abiliti ® system provides tailored gastric electrical stimulation activated by food entry into the stomach and sensor‐based data to medical professionals. The aim of this study was to analyze behavior changes using sensor‐based food intake and activity data in participants treated with the CLGES system. Methods: Food intake and activity data (3D accelerometer) were downloaded at baseline and monthly/bimonthly for 12 months in a subset of patients with obesity ( N  = 45) participating in a multicenter trial with CLGES. Measured food intake parameters included the number of intakes during allowed and disallowed periods, nighttime intakes, and between‐meal snacks (average/d). Activity parameters included time in different levels of physical activity (min/d), sleep/sedentary (h/d), and estimated energy expenditure (EE). Results: Weight loss at 12 months averaged 15.7 ± 7.7% of the baseline body weight. Stable reduction in the number of disallowed meals and between‐meal snacks ( P  < 0.05), an increase in all levels of physical activity ( P  < 0.001), and an increase in activity‐based EE (303 ± 53 kcal/d on average, P  < 0.001) were seen. Conclusions: Significant improvement in eating and activity was seen in participants. It is hypothesized that feedback of the sensor‐based data induced behavioral changes and contributed to weight loss in patients treated with CLGES.